2019
DOI: 10.1074/jbc.ra118.006801
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between N-terminal and C-terminal domains in stromal interaction molecule 2 (STIM2) determines enhanced STIM2 sensitivity

Abstract: Edited by Roger J. Colbran Store-operated Ca 2؉ entry (SOCE) is a ubiquitous pathway for Ca 2؉ influx across the plasma membrane (PM). SOCE is mediated by the endoplasmic reticulum (ER)-associated Ca 2؉-sensing proteins stromal interaction molecule 1 (STIM1) and STIM2, which transition into an active conformation in response to ER Ca 2؉ store depletion, thereby interacting with and gating PM-associated ORAI1 channels. Although structurally homologous, STIM1 and STIM2 generate distinct Ca 2؉ signatures in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 59 publications
2
40
0
2
Order By: Relevance
“…The fluorescence intensity was quantified using LAS X (Leica microsystems) software. Intracellular Ca 2+ measurements Intracellular Ca 2+ imaging was performed described previously (Emrich et al, 2019;. Briefly, the cells were cultured on glass coverslips with 50-60% confluency.…”
Section: Mitochondrial Ca 2+ Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence intensity was quantified using LAS X (Leica microsystems) software. Intracellular Ca 2+ measurements Intracellular Ca 2+ imaging was performed described previously (Emrich et al, 2019;. Briefly, the cells were cultured on glass coverslips with 50-60% confluency.…”
Section: Mitochondrial Ca 2+ Measurementsmentioning
confidence: 99%
“…The statistics were calculated by One-way ANOVA followed by post-hock Tukey's test except for B, D, and F where paired t-test was performed, *p≥0.05, **p≥0.01, ***p≥0.001 Wigerup, C., Påhlman, S., & Bexell, D. (2016) 7, 939-946. doi:10.1038/cdd.2009.16 Zhang, X., Pathak, T., Yoast, R., Emrich, S., Xin, P., Nwokonko, R. M., . .…”
Section: Glucose and Lactate Measurementsmentioning
confidence: 99%
“…Next, we determined the functional significance of the N-terminal versus the C-terminal domains of each STIM isoform in regulating Ca 2+ oscillations by utilizing two chimeric constructs that we recently developed 40 . The first chimera consists of the N-terminal and transmembrane domains of STIM1 combined with the C-terminus of STIM2 (tk-S1N-S2C) while the second consists of the N-terminal and transmembrane domains of STIM2 combined with the C-terminus of STIM1 (tk-S2N-S1C).…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the known properties of NFAT1, which requires robust Ca 2+ concentrations for activation and with STIM1 function described herein as the exclusive driver of Ca 2+ plateaus. We recently revealed that coordination between endogenous STIM1 and STIM2 plays a critical role in mediating SOCE in the colorectal cancer cell line HCT116 40 . Further, recent studies presented evidence that STIM2 can serve as an enhancer of receptor-activated Ca 2+ signaling by recruiting STIM1 to Orai1 channels under conditions of modest store depletion 33,37,38 , in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…We observed an increase in oscillation frequency but a decrease in the average amplitude of these oscillations in neurons in the optic tectum in stim2a −/− zebrafish compared with WT fish. It was shown earlier that STIM2 deletion and the subsequent SOCE disruption caused the decrease in oscillations of non-neuronal cells [ 66 , 67 ]. However, our in vivo data showed the increased Ca 2+ oscillation frequency in brain neurons stim2a −/− mutants.…”
Section: Discussionmentioning
confidence: 99%